Semaphorin3C identified as mediator of neuroinflammation and microglia polarization after spinal cord injury - Junjie Shen; Liangzhi Gong; Yi Sun; Junqing Lin; Wencheng Hu; Jiabao Wei; Xin Miao; Tao Gao; Jinlong Suo; Jia Xu; Yimin Chai; Bingbo Bao; et al. (iScience, 2024)
Summary: Excessive neuroinflammation after spinal cord injury (SCI) is a major hurdle during nerve repair. Although proinflammatory macrophage/microglia-mediated neuroinflammation plays important roles, the underlying mechanism that triggers neuroinflammation and aggravating factors remain unclear. The present study identified a proinflammatory role of semaphorin3C (SEMA3C) in immunoregulation after SCI. SEMA3C expression level peaked 7 days post-injury (dpi) and decreased by 14 dpi. In vivo and in vitro studies revealed that macrophages/microglia expressed SEMA3C in the local microenvironment, which induced neuroinflammation and conversion of proinflammatory macrophage/microglia. Mechanistic experiments revealed that RAGE/NF-κB was downstream target of SEMA3C. Inhibiting SEMA3C-mediated RAGE signaling considerably suppressed proinflammatory cytokine production, reversed polarization of macrophages/microglia shortly after SCI. In addition, inhibition of SEMA3C-mediated RAGE signaling suggested that the SEMA3C/RAGE axis is a feasible target to preserve axons from neuroinflammation. Taken together, our study provides the first experimental evidence of an immunoregulatory role for SEMA3C in SCI via an autocrine mechanism.